Every man has his price: Kant's argument for universal radical evil. Issue 4 (21st April 2022) - Indregard, Jonas Jervell
ABSTRACT: Kant famously claims that we have all freely chosen evil. This paper offers a novel account of the much-debated justification for this claim. I reconstruct Kant's argument from his affirmation that we all have a price – we can all succumb to temptation. I argue that this follows a priori from a theoretical principle of the Critique of Pure Reason, namely that all empirical powers have a finite, changeable degree, an intensive magnitude. Because of this, our reason can always be overpowered by sensible inclinations. Kant moreover holds that this necessary feature of our moral psychology should not have been the case: We ought to instead be like the divine human being, for whom the moral law yields a greater incentive than any possible temptation. On Kant's view, we are thus responsible for having a price, and the synthetic a priori fact that we do proves that we each made an initial choice of evil.